Dynamical integrated framework development of solid waste management in Malaysia - Faridah, Zulkipli; Zulkifli, Mohd Nopiah; Noor Ezlin, Ahmad Basri; Kie, Cheng Jack (Science Publishing Corporation Inc., 2018)
The paper is an illustrated of the framework development on dynamical integrated solid waste management in Malaysia. The framework is consisted of four stages. First stage is an essential study done by authors for understanding the solid waste management process and identifying the related issues by engaging an expert of the field and previous studies. Second stage is highlighted the important of predicting an adequate quantity of the waste generation in Malaysia. The prediction process applied a multilinear regression analysis. Third stage presented a development of integrated dynamical solid waste management model using system dynamics simulation. In the final stage, a user interface is constructed for assisting an operational level to monitor the progression of their performance on strategic plan. This summary conceptual framework represents the holistic framework which significantly assist the operational department for monitoring the solid waste management process efficiently and comprehensively.